Association Between Coeliac Disease and Risk of Any Malignancy and Gastrointestinal Malignancy. Issue 38 (September 2015) - Han, Yuehua; Chen, Wuzhen; Li, Peiwei; Ye, Jun; Pezzilli., Raffaele
<x xml:space="preserve">Abstract</x> Abstract Coeliac disease (CD) is reported to be associated with risk of malignancy; however, this association remains unclear. We aimed to systematically evaluate the association between CD and risk of all malignancies as well as gastrointestinal (GI) malignancy specifically. The PUBMED and EMBASE databases were searched to identify eligible studies from 1960 to March 2015, without restriction. Two reviewers independently performed the study inclusion and data extraction methods. Odds ratios (ORs), risk ratios, or standardized incidence ratios were pooled using either a fixed- or a random-effects model. Sensitivity and subgroup analyses were used to explore sources of heterogeneity. A total of 17 studies were included in this meta-analysis. The pooled OR for risk of all malignancies was 1.25 (95% confidence interval [CI] 1.09–1.44), whereas the pooled OR for risk of GI malignancy was 1.60 (95% CI 1.39–1.84) and suggested an inverse association with CD. Moreover, patients with CD were at a higher risk of esophageal cancer (pooled OR = 3.72, 95% CI 1.90–7.28) and small intestinal carcinoma (pooled OR = 14.41, 95% CI 5.53–37.60), whereas no significant associations were observed for other GI cancers, including gastric, colorectal, liver, and pancreatic cancers. Subgroup analyses also indicated that the results were influenced by the CD diagnostic method, as well as the follow-up time after CD diagnosis. CD was associated with increased risk of all malignancies as well as GI malignancies, including esophageal cancer and small intestinal carcinoma.